P679 Is the burden of obesity in IBD bigger than just weight?. (30th January 2023) - Madigan, S; Mountifield, R; Barnes, A
Abstract: Background: In the past IBD has been thought to cause low body weight however current estimates show that 15-40% of those with IBD are obese. Obesity is a pro-inflammatory state and has been linked to disease processes such as psoriasis and rheumatoid arthritis. There is some limited data to suggest that obesity also affects disease activity in IBD. In addition, medical therapy for IBD such as corticosteroids and TNF-alpha inhibitors are associated with weight gain. The aim was to determine the relationship between obesity and IBD disease severity. And also to determine the relationship between obesity, depression, anxiety and QoL in those with IBD. Methods: As part of the IBD-SLEEP study a survey was emailed to patients via tertiary hospital IBD unit email lists, private gastroenterology group email lists and advertised online. IBD activity was assessed using the Harvey Bradshaw Index and the Simple Crohn's Colitis index as appropriate. The survey included measures of clinically significant depression (PHQ9>10) and anxiety (GAD7>10), as well as disability (IBD-DI reduced form) and quality of life (EQ-5D-5L). Results: They were 585 responses with mean age of 42 years (SD 13). The majority were female (80%) and had Crohn's disease (61%). Mean weight of cohort was 79.2kg (SD 20), mean BMI was 28 (SD 7), with 61% overweight (BMI > 25), and 38% obese (BMI>30). People with obesity were more likely to have active disease (HBI or SCCAI > 5) in those with Crohn' disease (OR 2.39 (1.47-3.89), p<0.001) but not ulcerative colitis (OR 1.26 (0.68-2.31), p=0.46). Obese patients were also found to have higher levels of disability (IBD-DI reduced form, p<0.001) and lower quality of life (EQVAS, p<0.001). Interestingly there was an association between obesity and depression (PHQ9>10, OR 2.06 (1.42-2.99), p<0.001) but not obesity and anxiety (GAD7>10, OR 1.03, (0.74-1.45), p=0.16). Conclusion: Obesity is not only a risk factor for metabolic disease but is also associated with active IBD in those with Crohn's disease. Obesity was also associated with clinically significant depression, increased disability, and lower quality of life. Although causation is not established, consideration should be given to more aggressive management of obesity in an IBD outpatient setting.